Financial Statement Fraud With Analysis Fraud Diamond Theory in pharmaceutical sub-sector manufacturing companies listed on the IDX in 2015-2019: Pendeteksian Financial Statement Fraud Dengan Analisa Fraud Diamond Theory (Pada Perusahaan Manufaktur, Sub Sektor Farmasi Yang Terdaftar Di Bei Periode 2015-2019) - Windi Arifa Syahadatina; Heni Agustina (Universitas Nahdlatul Ulama Surabaya, 2020)
This study aimsto detect Financial Statement Fraud With Analysis Fraud Diamond Theory in pharmaceutical sub-sector manufacturing companies listed on the IDX in 2015-2019. The data used inthis study aresecondary data from the company's annual financial statements. In this study using quantitative methods with a descriptive analysisap proach. The population used in this research are pharma ceutical company eslisted on the IDX in 2015-2019. This method uses the desired sampling method with a sample size of 7 samples that meet the criteria. Data analysis used logistic regression using SPSS. The results of this study indicate that pressure, opportunity, rationalization, capability have an effect on financial statement fraud.